ON THE PROBLEMS OF INTEGRATING DIGITAL TECHNOLOGIES INTO THE EDUCATIONAL PROCESS. (Conference Zone, 2022)
This article discusses implementation question of digitalization which effects as content of the education and its organization. Native teacher of transferred knowledge and skills becomes orienting of students in the knowledge base. Urgency of problem consists in identifying the main directions for integration in the education process of university of general digitalization.